Lung decortication in phase III pleural empyema by video-assisted thoracoscopic surgery (VATS) : results of a learning curve study - Reichert, Martin; Pösentrup, Bernd; Hecker, Andreas; Padberg, Winfried; Bodner, Johannes; Justus Liebig University Giessen (My University, 2018)
Background: Pleural empyema (PE) is a devastating disease with a high morbidity and mortality. According to the American Thoracic Society it is graduated into three phases and surgery is indicated in intermediate phase II and organized phase III. In the latter, open decortication of the lung via thoracotomy is the gold standard whereas the evidence for feasibility and safety of a minimally-invasive video-assisted thoracoscopic approach is still poor.Methods: Retrospective single-center analysis of patients undergoing surgery for phase III PE from 02/2011 to 03/2015 [n=138, including n=130 VATS approach (n=3 of them with bilateral disease) and n=8 open approach]. The learning curve was assessed by grouping those 127 patients with unilateral disease who underwent a video-assisted thoracoscopic approach into two groups: VATS-1 (03/2011 to 06/2012, n=43) and VATS-2 (06/2012 to 03/2015, n=84).Results: ASA-scores (P=0.0279) and rate of pre-operative drainage therapy (P=0.0534) were higher in VATS-2 patients. Operating times were longer in VATS-1 (P=0.0308), intra-operative complication as well as conversion to open surgery rates did both not differ. Rates of post-operative vasoconstrictive therapy (P=0.0191) and prolonged mechanical ventilation (P=0.0560) were both higher in VATS-2, however, post-operative length of stay (LOS) at intensive care unit, overall post-operative LOS and post-operative complication rate were similar in both groups.Conclusions: Video-assisted thoracoscopic surgery is feasible for evacuation and decortication in late phase III PE. A learning curve of approximately 40 cases is sufficient to gain procedure-specific surgical skills and thus reduce the operating times sufficiently.
Keywords: Video-assisted thoracoscopic surgery (VATS); learning curve; pleural empyema (PE); lung decortication; ddc:610